Un análisis comparativo de los enfoques de gestión de Proyectos Cascada y Scrum y su implementación en aplicaciones móviles. - Freire Morales, Andrea Katherine (2024)
Mobile app development is an integral part of the digital strategy of many organizations today. However, effective project management in this area can be a crucial challenge in ensuring the success of the final product. In this study, a comprehensive comparative analysis is performed on two project management approaches widely used in software development: the waterfall approach and the agile approach represented by Scrum. Several key aspects are examined, including efficiency, final product quality, adaptability to change, customer satisfaction, and delivery time. The goal is to provide companies with a clear view of the strengths and weaknesses of each approach in the specific context of mobile application development, in order to help them make informed decisions and optimize their development processes.